Effects of urbanization and lifestyle habits on the intestinal microbiota of adolescents in eastern China - Zhao, Gang; Xie, Lu; Wu, Yan; Wang, Bing; Teng, Weilin; Sun, Zhou; Kao, Qingjun; Liu, Wei; Pi, Xionge; Ma, Haiyan (Frontiers in Microbiology, 2023)
Owing to urbanization, living habits have changed widely, leading to alterations in the intestinal microbiota of urban residents. A total of 302 fecal samples collected from adolescent students in eastern China were examined. 16S rRNA high-throughput sequencing was used to identify the fecal microbiota. These data were combined with questionnaire survey results to investigate the effect of urbanization on the intestinal microbiota of adolescents in eastern China. Moreover, the role of lifestyle habits in this relationship was also evaluated. The results revealed signifi-cant differences in the structure of the intestinal microbiota among adolescents living in regions with different levels of urbanization. Adolescents living in urban regions had a significantly higher proportion of Bacteroides (P < 0.001, FDR = 0.004), whereas those living in towns and rural regions had higher proportions of Bifidobac-terium (P < 0.001, FDR < 0.001) and Prevotella (P < 0.05, FDR = 0.019). The diver-sity of the intestinal microbiota was higher in urban residents than in adolescents liv-ing in towns and rural regions (P < 0.05). In addition, the differences in intestinal mi-crobiota across individuals living in cities, towns, and rural regions were related to dietary preferences, flavor preferences, and sleep and exercise durations. Adolescents who ate more meat had more Dorea (LDA = 3.622, P = 0.04), while the abundance of Escherichia-Shigella is higher among adolescents who ate more condiments (LDA = 4.285, P = 0.02). The abundance of Dialister was significantly increased in adoles-cents with longer sleep durations (LDA = 4.066, P = 0.03). Adolescents who exer-cised for a long duration had more Faecalibacterium than those who exercised for a shorter duration (LDA = 4.303, P = 0.04). These results deliver insights into the ef-fects of lifestyle and provide a scientific basis for the maintenance of a healthy intes-tinal microbiota in adolescents.